PERSONAL EXPERIENCING OF THE MACEDONIAN EPIC FOLK SONGS - Marijana Markovikj; Eleonora Serafimovska (INSTITUTE FOR SOCIOLOGICAL, POLITICAL AND JURIDICAL RESEARCH UNIVERSITY “Ss. CIRYL AND METHODIUS” - SKOPJE, 2016)
In the course of the past centuries, the Macedonian folk song embraced all significant moments of the lives of the Macedonian people. These songs pay tribute to the years of servitude, resistance, military feats, whether individual or group, spontaneous or organized. Throughout the conducted research, the question we focused on was whether these Macedonian songs created in the course of the 19th century -period of active struggle for liberation and independence of the Macedonian nation; evoke feelings of patriotism among the young in contemporary time when the Republic of Macedonia has acquired its sovereignty and independence. For the purpose of determining the influence of music on the emotions, and identifying the emotions, thoughts, ideas and behavior ‘touched upon’ and evoked by the Macedonian epic folk song, experimental research was conducted. The experiment was realized in a time period of 2 hours with a group of 18 students that participated on a voluntary basis. The findings from the analysis of the emotions experienced by the respondents in the experiment indicate that the respondents can identify the different emotions, thoughts and ideas embodied in two popular Macedonian epic folk songs. Hence, these epic songs (especially when listened with lyrics) not only evoke negative emotions but cause negative thoughts and ideas as well. In this sense, the main conclusion is that the Macedonian epic folk songs created in 19th century still “‘touch upon” the present generations.
Keywords: Macedonian epic folk song, emotions, cognition